SARS‐CoV‐2 infections among neonates born to pregnant people with SARS‐CoV‐2 infection: Maternal, pregnancy and birth characteristics. Issue 4 (18th April 2022) - Olsen, Emily O'Malley; Roth, Nicole M.; Aveni, Kathryn; Santos, Pauline; Sizemore, Lindsey; Halai, Umme‐Aiman; Nestoridi, Eirini; Barton, Jerusha Elana; Mobley, Evan; Siebman, Samantha; Fussman, Chris; Mbotha, Deborah; et al.
Abstract: Background: Multiple reports have described neonatal SARS‐CoV‐2 infection, including likely in utero transmission and early postnatal infection, but published estimates of neonatal infection range by geography and design type. Objectives: To describe maternal, pregnancy and neonatal characteristics among neonates born to people with SARS‐CoV‐2 infection during pregnancy by neonatal SARS‐CoV‐2 testing results. Methods: Using aggregated data from the Surveillance for Emerging Threats to Mothers and Babies Network (SET‐NET) describing infections from 20 January 2020 to 31 December 2020, we identified neonates who were (1) born to people who were SARS‐CoV‐2 positive by RT‐PCR at any time during their pregnancy, and (2) tested for SARS‐CoV‐2 by RT‐PCR during the birth hospitalisation. Results: Among 28, 771 neonates born to people with SARS‐CoV‐2 infection during pregnancy, 3816 (13%) underwent PCR testing and 138 neonates (3.6%) were PCR positive. Ninety‐four per cent of neonates testing positive were born to people with infection identified ≤14 days of delivery. Neonatal SARS‐CoV‐2 infection was more frequent among neonates born preterm (5.7%) compared to term (3.4%). Neonates testing positive were born to both symptomatic and asymptomatic pregnant people. Conclusions: Jurisdictions reported SARS‐CoV‐2 RT‐PCR results for only 13% of neonates known to be born to people with SARS‐CoV‐2 infection during pregnancy. These results provide evidence of neonatal infection identified through multi‐state systematic surveillance data collection and describe characteristics of neonates with SARS‐CoV‐2 infection. While perinatal SARS‐CoV‐2 infection was uncommon among tested neonates born to people with SARS‐CoV‐2 infection during pregnancy, nearly all cases of tested neonatal infection occurred in pregnant people infected around the time of delivery and was more frequent among neonates born preterm. These findings support the recommendation for neonatal SARS‐CoV‐2 RT‐PCR testing, especially for people with acute infection around the time of delivery.